Inventarisasi Tanaman Berkhasiat Obat di Desa Gololada Kabupaten Manggarai Timur - Klaudia Marlina Magung; Samuel David I. Makoil (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2026)
Background: Medicinal plants are biological resources traditionally used by communities based on knowledge passed down through generations. However, changes over time may lead to the loss of this knowledge, making documentation and inventory essential for preserving local wisdom. Objective: This study aimed to inventory medicinal plants used by traditional healers (hatra) in Gololada Village, East Manggarai Regency, including plant types, parts used, processing methods, properties, and rules of use. Methods: This research employed a descriptive method with an observational design. Data were collected through observation, structured interviews, and documentation involving seven traditional healers selected using purposive sampling. Data were analyzed descriptively. Results: The study identified 32 medicinal plant species. Leaves were the most frequently used plant part (60.60%), while boiling was the most common processing method (51.85%). The plants were used to help treat various health problems, including digestive disorders, hypertension, diabetes, kidney stones, skin diseases, coughs, rheumatism, and insomnia, as well as to increase endurance. The most common usage frequency was once daily. Conclusion: Traditional healers in Gololada Village continue to maintain the use of medicinal plants as part of traditional medicine. The inventory provides information to support the preservation of local wisdom and future medicinal plant research.